Integrasi Hukum Agraria dan Tata Ruang dalam Pengendalian Alih Fungsi Lahan: Analisis Yuridis atas Disharmoni Regulasi di Indonesia - Naylin Putri Harsa; Raisa Qolbina Ibrizzahra; Nazjwa fatharani; Agil Sabani; Muhammad Adymas Hikal Fikri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the legal integration between agrarian law and spatial planning law in controlling land-use conversion in Indonesia, focusing on the regulatory disharmony between Law Number 5 of 1960 concerning Basic Agrarian Principles and Law Number 26 of 2007 concerning Spatial Planning. The research aims to identify the forms of normative disharmony, analyze their implications for land-use control, and formulate an integrative legal harmonization model. This study employs a normative juridical method using statutory, conceptual, and case approaches through the analysis of legislation, legal doctrines, and judicial decisions. The findings reveal that regulatory disharmony originates from fragmented legal norms, sectoral institutional arrangements, and the absence of an integrated normative framework linking land administration with spatial planning, resulting in horizontal and vertical conflicts of norms that undermine legal certainty in controlling land-use conversion. The study further finds that systematic and teleological legal interpretation provides the basis for reconstructing legal integration through a Model of Integrative Harmonization of Agrarian and Spatial Planning Law, which connects the social function of land, spatial conformity, and institutional coordination within a unified legal framework. This model constitutes the principal novelty of the research by offering a normative framework for strengthening legal integration and promoting sustainable land governance in Indonesia